MODEL PEMILIHAN SERVER SIDE SCRIPTING UNTUK SISTEM INFORMASI SEKOLAH: STUDI KOMPARASI ASP, JSP, PHP, PYTHON, DAN RUBY - Dewi Mustari (Jurnal Sistem Informasi, 2015)
There are many criteria that could be used as the basis for the selection of server side scripting that could be applied to the school information system. This study compares several server side scripting that could be applied the school information system. Those server side scripting are ASP, JSP, PHP, Python, and Ruby. This research refers to research done by Oyku Alanbay regarding the selection of softwares. In addition, using the theories regarding the quality of the software as the basis for the determination of selection sub criteria server side scripting to the school information system. In the selection of server side scripting for this school information system with three levels of criteria. As for the level 1 criteria is technology related, user related, and vendor related, level 2 criterion consists of 18 sub criteria obtained from the special advantages for server side scripting. And level 3 there are five alternatives is ASP, JSP, PHP, Python, and Ruby. In the selection of server side scripting for this school information systems using Analytical Hierarchy Process (AHP) and the tool uses Expert Choice 2000. The results of this election make PHP as server side scripting needs compared to ASP, JSP, Python, and Ruby with 40.6% weighting values with the most influential factor was 60.4% of the user related.